Investigating the Effective Factors on the Productivity and Empowerment of Human Resources of the General Directorate of Sports and Youth of Qazvin Province - Rahimi Niaraki, Mahdi; Mokhtari, Mohammad Ali (International journal of industrial engineering and operational research, 2024)
Attention to human resources in organizations has taken a significant portion of the time and capital of leading organizations in recent years. Smart managers now understand that no matter how much they invest in developing and promoting human resources and productivity, they ensure their organization's success, efficiency, and competitive advantage. It has been claimed that the most effective way to gain a competitive advantage in organizational settings is to enhance the efficiency and empowerment of human resources, especially considering the tremendous changes and developments. Therefore, productivity has been discussed and investigated to empower the organization's human resources. This research examines the factors affecting the productivity and empowerment of human resources in the General Directorate of Sports and Youth of Qazvin Province. This study is of a survey and applied type, utilizing a questionnaire as the data collection tool, with field data collection methods taken into account. The statistical population of this research comprises all managers, deputies, experts, employees, and heads of the Qazvin Province Sports and Youth Directorate sports teams, with Cochran's formula applied for sampling. This study used structural equation modeling to analyze the data, employing LISREL software. Initially, the indicators were identified, and hypotheses were developed based on these indicators. Finally, using statistical techniques, all proposed hypotheses were validated, leading the researcher to conclude that the proposed factors significantly impact the productivity and empowerment of human resources in the General Directorate of Sports and Youth of Qazvin Province.